The Existence of the Kyai Upas Spear Ceremony as the Identity of the Local Community of Tulungagung - Ramadhanty Putri, Virza; Hudiyanto, R. Reza; Utami, Indah Wahyu Puji; Wahyudi, Deny Yudo (Universitas Muhammadiyah Malang, 2026)
Tulungagung Regency, East Java is one of the districts that has an interesting tradition that is carried out by residents every year because it is related to the history of Tulungagung in the past when the Kingdom of Mataram was still standing in the land of Java. The Jamasan Pusaka Pusaka Tombak Kyai Upas Traditional Ceremony is a tradition that is routinely carried out every year. The research method used in this study uses the Gray method and participatory observation that focuses on anthropology to study cultural events, documentation collection and life views of the research subjects. The Kyai Upas spear, a historical heirloom of the folklore of Ki Wonoboyo and Baru Klinthing, is believed to protect the community from disasters and maintain peace, becoming the cultural identity of Tulungagung. Based on research, the Jamasan Ceremony, which was held after 10 Sura at the Kepatihan Archives Office, involved carnivals, flushing, greetings, and puppet shows, reflecting the values of mutual cooperation, preservation of Javanese culture, religiosity, and nationalism. This tradition strengthens local identity, shows the connection of humans with nature and history, and is a form of gratitude and respect for the ancestral heritage that continues to live in the Tulungagung community